2019
DOI: 10.1515/mgmc-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Thermal rearrangement of a 1,2-bis(silylene): Synthesis and crystal structure of a silyl-silylene

Abstract: Thermal rearrangement of the 1,2-bis(silylene), [{(4-ButPh)C(NDip)2}Si−]2 (Dip = 2,6-diisopropylphenyl, leads to the silyl-silylene, {(4-ButPh)C(NDip)2}Si−Si(H) {N(Dip)C(=NDip)(4-ButPh-H)}, via an intramolecular C−H activation reaction. The X-ray crystal structure, and limited spectroscopic data, for the compound are reported. The structure of the silyl-silylene incorporates an exocyclic imine fragment, which is unprecedented for this compound class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In contrast, no reaction occurred between CO and the germanium and tin analogues of 1 , viz . [{ArC(NDip) 2 }M] 2 (M=Ge or Sn), under ambient conditions [6] . It appears that compound 2 is formed by a combination of Si−Si bond cleavage, and insertion of CO into an N−Si bond of one four‐membered silylene ring of the starting material, 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, no reaction occurred between CO and the germanium and tin analogues of 1 , viz . [{ArC(NDip) 2 }M] 2 (M=Ge or Sn), under ambient conditions [6] . It appears that compound 2 is formed by a combination of Si−Si bond cleavage, and insertion of CO into an N−Si bond of one four‐membered silylene ring of the starting material, 1 .…”
Section: Methodsmentioning
confidence: 99%
“…5 It is noteworthy, however, that a small number of other 1,2-disilylenes are known, 2,6 and have showed reactivity related to that of [{PhC(NBu t ) 2 }Si] 2 . While the further chemistry of 1 is sparse, 7 we have recently showed that it reacts cleanly with CO under ambient conditions to give an unprecedented example School of Chemistry, PO Box 23, Monash University, VIC, 3800, Australia. E-mail: cameron.jones@monash.edu; https://www.monash.edu/science/researchgroups/chemistry/jonesgroup of an "abnormal" N-heterocyclic silylene, 2 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…5 It is noteworthy, however, that a small number of other 1,2-disilylenes are known, 2,6 and have showed reactivity related to that of [{PhC(NBu t ) 2 }Si] 2 . While the further chemistry of 1 is sparse, 7 we have recently showed that it reacts cleanly with CO under ambient conditions to give an unprecedented example of an “abnormal” N-heterocyclic silylene, 2 (Fig. 1), which is functionalised by an oxysilylene fragment.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In contrast to [{PhC(NBu t ) 2 }Si] 2 , the reactivity of 1 has been poorly studied. [6] However, given that its SiÀ Si bond has been calculated to be very weak (16.6 kcal mol À 1 ), and longer (2.488(2) Å) than that in [{PhC-(NBu t ) 2 }Si] 2 (2.413(2) Å), it might be expected to display similar, if not greater, reactivity than Roesky's 1,2-disilylene.…”
mentioning
confidence: 99%
“…[{ArC(NDip) 2 }M] 2 (M = Ge or Sn), under ambient conditions. [6] It appears that compound 2 is formed by a combination of SiÀ Si bond cleavage, and insertion of CO into an NÀ Si bond of one four-membered silylene ring of the starting material, 1. The product, 2, can be formulated as a bis(silylene), which contains one four-membered silylene fragment linked to a five-membered silylene ring via an Oatom bridge.…”
mentioning
confidence: 99%